Writers in Austria on the war in Ukraine (Elfriede Jelinek, Julya Rabinowich and Peter Paul Wiplinger) - Jaworska, Aleksandra (Transfer. Reception Studies, 2022)
The article contains statements by authors addressed to the Russian public. The Austrian writer and Nobel Prize winner Elfriede Jelinek published an article Ukraine on her website with a message to the Russians and Russia. Julya Rabinowich, a writer from the for-mer Soviet Union who now lives in Austria, also commented on the same issue in her com-mentary Zensur gebiert Monster [Censorship gives birth to monsters]. The Austrian writer Peter Paul Wiplinger, on the other hand, critically addressed the Russian dictator's actions in his two poems Alle, die töten [All who kill] and Herr Putin ist besorgt [Mr Putin is worried], pub-lished on schoepfblog.at.